Балканизмот/византизмот како ресемантизирана меморија (споделена точка на допир во културната историја на Балканот) - Banovikj-Markovska, Angelina (БАН, София, 2017)
This essay is based on the premise that in these areas there is one specific cultural memory, which could be not only an important link for understanding and interpreting the Balkan's past, but the starting point for future dialogue forms. It takes into account recalling and forgetting - recalling as an ability to recall into our memories past events and times, while forgetting as a suppressed type of "experience" which functions both as the source and the depository of our knowledge. This could contribute to the creation of a (re) semanticized memory, that would not be burdened by the ethnogenesis of the Balkan peoples, but with the shared "sites of memory", with potential points of contact, which reveal who we are, based on what we no longer are. In this respect, the terms milieux de mémoire and lieux de mémoire from Pierre Nora's concept seemed exceptionally important and adequate. The former as entry into the mnemonic restructuring of the lived collective memory in the Balkans (which led to the creation of an internalized, sedimentary and commemorative memory), while the latter as the key for mnemonic deconstruction of that inherited memory and for creating an externalized counter-memory, which in the symbolic displays, sites and ideals of the Balkan cultural history, would recognise the common, referential and almost productive "points of contact". In this essay I will focus on Balkanism/Byzantism as a shared "memory site" whose cultural mission - redefining the contaminated image of the Balkans - paves the way towards horizontal and vertical integration of Balkan peoples and cultures.
Keywords: Balkans; cultural memory; Byzantism; Balkanism; points of contact; sites of memory